Comparación de métodos de interpolación para la generación de Mapas de Ruido en entornos urbanos (2012)
This paper presents a study focused on the analysis of the congruence of interpolation methods for creating noise maps. For this purpose noise measurements were performed in two areas of Medellin - Colombia- in compliance with the National Standard 0627 issued in 2006. Subsequently, this information was analyzed in the software for geographic information systems called ArcGIS. To obtain the noise curves the Kriging and IDW interpolation methods were used, varying the configuration of the input parameters and performing a statistical analysis to determine which model had more accurate results. Finally, an assessment was made by comparing the resultant noise map with the issues established by Colombian laws